Low-carbon concrete prepared based on brick slag matched with metal tailings and preparation method of low-carbon concrete
By enhancing modification and hydrophobic modification of waste brick slag, the problem of reduced compressive strength and crack resistance when traditional concrete uses waste brick slag is solved, and efficient resource reuse and carbon emission reduction are achieved.
Patent Information
- Application Number
- CN202411916665.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-24
AI Technical Summary
When traditional concrete uses waste brick slag as aggregate, compressive strength and crack resistance are reduced, and the high water absorption and porosity of waste brick slag lead to uneven distribution of moisture, affecting the durability of concrete.
By enhancing modification and hydrophobic modification of waste brick slag, its mechanical properties and crack resistance are improved. The specific method includes immersion in a modified mixed solvent containing silane coupling agent, binder, water and crack filler, and conducting high-temperature treatment in a hydrophobic modified solution to reduce its water absorption rate.
It significantly improves the compressive strength and crack resistance of concrete, extends its durability, and realizes resource reuse of waste waste, reducing dependence on natural resources and carbon emissions.
Smart Images

Figure BDA0005206975330000101
Abstract
Description
Technical Field
[0001] The present application relates to the field of building materials, and more specifically, to a low-carbon concrete prepared based on brick slag and metal tailings and a preparation method thereof. Background Art
[0002] With the rapid development of social economy and the acceleration of urbanization, the construction of a large number of buildings has brought huge demand for building materials. Traditional concrete consumes a lot of natural resources such as sand, gravel, cement, etc. and emits a lot of carbon dioxide during the production process. At the same time, a large amount of construction waste is generated every year in recent years, especially the demolished buildings are mostly brick-concrete structures. Among the construction waste generated by the demolition of these buildings, construction waste bricks account for a considerable proportion. How to achieve the recycling of these construction waste bricks has been widely studied.
[0003] In recent years, in order to reduce the carbon footprint of the construction industry, the use of industrial waste as an alternative material to prepare new concrete has begun to be explored. Industrial waste includes but is not limited to fly ash, slag, brick slag, furnace slag, etc. In particular, the reuse of a large amount of brick slag is of great significance for resource recycling and solving the problem of construction waste disposal.
[0004] However, compared with natural aggregates, waste brick slag has a large porosity, high water absorption rate, and its compressive strength is lower than that of natural aggregates. When it is directly added to concrete as an aggregate, the compressive strength of the concrete is reduced. At the same time, its water absorption and porosity cause stress inside the concrete. At the same time, its strong water absorption leads to uneven moisture distribution. In the subsequent drying process, shrinkage stress is generated due to the evaporation of water, which reduces the crack resistance of the concrete and its durability. Summary of the invention
[0005] In order to alleviate the problem of reduced compressive strength and crack resistance of concrete using waste brick slag as aggregate, the present application provides a low-carbon concrete prepared based on brick slag and metal tailings and a preparation method thereof.
[0006] In the first aspect, the present application provides a low-carbon concrete made from brick slag and metal tailings, using the following technical solution: A low-carbon concrete made from brick slag and metal tailings, comprising the following raw materials in parts by weight: 350-400 parts of cement, 145-180 parts of water, 620-760 parts of coarse aggregate, 260-350 parts of fine aggregate, 80-120 parts of mineral admixture, 40-60 parts of rice husk ash, 5-10 parts of admixture and 15-20 parts of anti-cracking fiber; Wherein, the coarse aggregate includes waste brick slag particles and crushed stone, the fine aggregate includes waste brick slag powder and sand, and the mineral admixture includes at least metal tailings; The waste brick slag powder and waste brick slag particles are obtained by crushing the waste brick slag, performing a reinforcing modification treatment, and then performing a hydrophobic modification treatment, and then crushing and grading to obtain waste brick slag particles and waste brick slag powder respectively; The enhanced modification treatment specifically comprises immersing the crushed waste brick slag in a modified mixed solvent containing a silane coupling agent, a binder, water and a crack filling filler and then subjecting the mixture to high temperature treatment.
[0007] By adopting the above technical scheme, mineral admixtures and rice husk ash are used in the present application to partially replace cement to reduce carbon emissions. Rice husk ash, as a low-carbon material, has excellent pore structure and active ingredients. Adding it to concrete can significantly improve the strength and durability of concrete, while reducing the amount of cement and carbon emissions. In addition, waste brick slag and metal tailings are added in the present application to replace part of the cement, reducing the amount of cement, thereby reducing the carbon emissions of concrete. It also solves the above-mentioned problem of waste dumping, realizes resource recycling, reduces dependence on natural resources, effectively utilizes industrial waste, and promotes sustainable development.
[0008] The high water absorption rate of waste brick slag is due to its high porosity on the one hand, and a large number of micro cracks are generated inside during the crushing process, which makes the compressive strength of the concrete used low and the crack resistance poor. Therefore, in the present application, the waste brick slag is subjected to a reinforcing modification treatment and then a hydrophobic modification treatment. This can improve the mechanical properties of the waste brick slag itself, thereby improving the compressive strength of the concrete, and on the other hand, the hydrophobic modification treatment can reduce the water absorption rate of the waste brick slag, thereby alleviating the subsequent reduction in crack resistance due to its high water absorption. In particular, in the present application, the waste brick slag is immersed in a modified mixed solvent containing a silane coupling agent, a binder, water and a crack filling filler and then subjected to a high temperature treatment. The crack filling filler is filled in the tiny cracks of the waste brick slag, and then the binder is used as a binder. It is combined with waste brick slag at the cracks and solidified during high temperature to achieve fixed sintering of microspheres and crack filling fillers. The intermediate phase asphalt and binder also form a continuous network structure under high temperature solidification and achieve filling of cracks, which not only improves the strength of the waste brick slag, but also improves its toughness, provides a stress buffer zone for subsequent concrete volume shrinkage, and improves its crack resistance. Finally, the modified and enhanced treatment in this application not only achieves the filling of microcracks in the waste slag powder, but also achieves a certain load of crack filling fillers in the pore structure of the waste slag powder, reduces its porosity, and improves its mechanical properties and crack resistance. Combined with subsequent hydrophobic modification treatment, the problem of reduced mechanical properties and crack resistance due to its high water absorption rate is further alleviated.
[0009] Optionally, the crack filling filler includes silica fume, fly ash and alkaline substances in a mass ratio of 1: (0.8-1.2): (0.5-0.8), and the alkaline substances are magnesium acetate and sodium aluminate in a mass ratio of 1: (1.2-1.5).
[0010] By adopting the above technical scheme, when silica ash and fly ash are added to the crack filling filler of the present application, the silica ash and fly ash have fine particle size and good filling performance, and can effectively fill the micro cracks in the waste brick slag, and the addition of magnesium acetate and sodium aluminate forms a soluble salt solution in the aqueous solution, so that the above soluble salt solution fully penetrates into the micro cracks of the waste brick slag, which helps to introduce sodium aluminate and magnesium acetate into the micro crack structure of the waste brick slag, and then high-temperature roasting is carried out, and the sodium aluminate reacts chemically with the silicate in the waste brick slag to generate a new compound, which can effectively fill the cracks, and the magnesium acetate solution penetrates into the cracks and reacts during the high-temperature roasting. Nano-magnesium oxide is formed and deposited in the cracks of the waste brick slag. In this way, the selection of crack filling fillers in the present application uses silica ash and fly ash to fill micro-cracks. For micro-cracks that are difficult to fill due to their size, the present application uses nano-magnesium oxide formed by the infiltration and subsequent calcination of magnesium acetate solution and sodium aluminate solution and the composite precipitate formed with waste brick slag, which not only fills the micro-cracks, but also forms a good transition compatible interface with the waste brick slag, thereby improving the mechanical properties of the waste brick slag. The addition of a binder can fix the above-mentioned filler and further supplement the filling effect, thereby significantly improving the performance of the waste brick slag.
[0011] Optionally, the modified mixed solvent comprises the following raw materials in parts by weight: 5-10 parts of silane coupling agent, 3-8 parts of adhesive, 20-30 parts of water, 15-20 parts of crack filling filler, 8-15 parts of aluminum sludge.
[0012] By adopting the above technical scheme, aluminum sludge is a waste product derived from water treatment and has a certain viscosity and plasticity. The addition of aluminum sludge in the present application allows the fine and colloidal substances in the aluminum sludge to penetrate into the microcracks of the waste brick slag, and gradually precipitate inside the cracks to achieve the filling of the microcracks of the waste brick slag. In addition, components such as alumina in the aluminum sludge may react with silicate components in the waste brick slag to generate more complex silicate or aluminate complexes, thereby achieving the filling of microcracks. After subsequent calcination, a certain skeleton structure is formed, thereby filling and supporting the large pores inside the waste brick slag to a certain extent, thereby improving the mechanical strength of the waste brick slag. The addition of silane coupling agent can improve the compatibility of the system, and is more conducive to dispersion in the system and filling in the waste brick slag.
[0013] Optionally, the binder is one or more of polyethylene glycol, hydroxyethyl cellulose, polyvinyl alcohol, and carboxymethyl cellulose.
[0014] By adopting the above technical scheme, when the above binder is selected, the modified mixed solvent has a certain bonding property, which is helpful for the bonding and fixation of raw materials such as crack filling fillers in the pores of waste brick slag. At the same time, the modified mixed solvent has better fluidity, which is helpful for the penetration and solidification of sodium aluminate and magnesium acetate solution in the crack filling filler into the waste brick slag, thereby improving the comprehensive performance of concrete.
[0015] Optionally, the high temperature treatment is specifically performed by first treating at 80-90° C. for 40-60 min, and then treating at 300-340° C. for 1-2 h.
[0016] Optionally, the specific operation of the hydrophobic modification treatment is: immersing the waste brick slag after the enhancement modification treatment in a hydrophobic modification solution and then drying it, the hydrophobic modification solution includes the following raw materials in parts by weight: 12-18 parts of versatate vinyl carbonate, 8-15 parts of mesophase asphalt microspheres, 5-10 parts of silane coupling agent, 1-3 parts of initiator, 5-12 parts of acrylamide, 5-10 parts of acryl alcohol and 20-30 parts of water.
[0017] By adopting the above technical scheme, when the waste brick slag is immersed in a hydrophobic modification solution for modification, tert-butyl vinyl carbonate, mesophase asphalt microspheres, acrylamide and acryl alcohol are added to the hydrophobic modification solution. The mesophase asphalt microspheres contain rich aromatic groups and unsaturated double bond groups. Therefore, in the present application, under the action of an initiator, tert-butyl vinyl carbonate reacts with the mesophase asphalt microspheres and the unsaturated bonds of acrylamide to form a hydrophobic polymer, and then forms a chemical bond with the waste brick slag that has been enhanced and modified under the action of a silane coupling agent. In this way, In order to achieve enhanced modification and hydrophobic modification of waste brick slag, reduce the problems of uneven stress distribution and reduced crack resistance due to its high water absorption, and the addition of acrylamide and acrylol in the present application introduces amino and hydroxyl functional groups, which can improve the compatibility of the modified waste brick slag in the concrete system, thereby achieving a balance between the water absorption and hydrophilicity of the waste brick slag, so that the hydrophobicity of the waste brick slag itself is improved and its water absorption rate is reduced. At the same time, the introduction of hydroxyl and amino groups improves the compatibility in concrete, thereby improving the compressive strength and crack resistance of the concrete.
[0018] Optionally, the coarse aggregate comprises waste brick slag particles and crushed stone in a mass ratio of 1:(0.6-0.8), and the fine aggregate comprises waste brick slag powder and sand in a mass ratio of 1:(0.4-0.6); The particle size of the waste brick slag particles is 5-10 mm, and the particle size of the waste brick slag powder is 0.2-0.35 mm.
[0019] By adopting the above technical solution, in the present application, the waste brick slag particles are processed to significantly increase their addition ratio in concrete while improving the mechanical properties and durability of the concrete.
[0020] Optionally, the mineral admixture is selected from slag, fly ash and gold tailings in a mass ratio of 1:(1.2-1.5):(2-3).
[0021] Optionally, the admixture is a polycarboxylate water reducer, and the anti-cracking fiber is one or more of glass fiber and polypropylene fiber.
[0022] By adopting the above technical solution and selecting the above mineral admixtures, the amount of cement can be reduced while ensuring the quality of concrete and at the same time achieving the recycling of industrial waste.
[0023] In the second aspect, the present application provides a method for preparing low-carbon concrete based on brick slag and metal tailings, using the following technical solution: A method for preparing low-carbon concrete based on brick slag and metal tailings comprises the following steps: Mixing cement, coarse aggregate, fine aggregate, mineral admixture, rice husk ash and anti-cracking fiber to prepare a primary mixture; The admixture is mixed with water to obtain a mixed solution, which is then added to the obtained primary mixture, and the mixture is stirred and mixed to obtain low-carbon concrete.
[0024] By adopting the above technical solution, the method provided by the present application is simple and convenient, and is easy to realize industrialization. In addition, the present application realizes the recycling of industrial waste, reduces the amount of cement used, reduces carbon emissions, and reduces dependence on natural resources.
[0025] In summary, this application has the following beneficial effects: 1. In the present application, the waste brick slag is subjected to a reinforcing modification treatment and then a hydrophobic modification treatment. In this way, on the one hand, the mechanical properties of the waste brick slag itself are improved, thereby improving the compressive strength of the concrete. On the other hand, the hydrophobic modification treatment can reduce the water absorption rate of the waste brick slag, thereby alleviating the subsequent reduction in crack resistance due to its high water absorption. In particular, in the present application, the waste brick slag is immersed in a modified mixed solvent containing a silane coupling agent, a binder, water and a crack filling filler and then treated at high temperature. The crack filling filler is filled in the tiny cracks of the waste brick slag, and then combined with the waste brick slag at the cracks under the action of the binder, and cured during the high temperature process to achieve fixed sintering of the microspheres and the crack filling filler, and the mesophase asphalt and the binder also form a continuous network under high temperature curing. The structure can fill the cracks, which not only improves the strength of the waste brick slag, but also improves its toughness; 2. The addition of aluminum sludge in the present application allows the fine and colloidal substances in the aluminum sludge to penetrate into the microcracks of the waste brick slag, and gradually precipitate inside the cracks to fill the microcracks of the waste brick slag. Moreover, the components such as alumina in the aluminum sludge may react with the silicate components in the waste brick slag to form more complex silicate or aluminate complexes, thereby filling the microcracks. After subsequent calcination, a certain skeleton structure is formed, thereby filling and supporting the large pores inside the waste brick slag to a certain extent, thereby improving the mechanical strength of the waste brick slag. The addition of silane coupling agent can improve the compatibility of the system, and is more conducive to the dispersion in the system and the filling effect in the waste brick slag; 3. The waste brick slag is immersed in a hydrophobic modification solution to achieve enhanced modification and hydrophobic modification of the waste brick slag, thereby reducing the problems of uneven stress distribution and reduced crack resistance due to its high water absorption. In addition, the addition of acrylamide and acrylol in the present application introduces amino and hydroxyl functional groups, which can improve the compatibility of the modified waste brick slag in the concrete system, thereby achieving a balance between the water absorption and hydrophilicity of the waste brick slag, thereby improving the hydrophobicity of the waste brick slag itself and reducing its water absorption rate. At the same time, the introduction of hydroxyl and amino groups improves its compatibility in concrete, thereby improving the compressive strength and crack resistance of the concrete. DETAILED DESCRIPTION
[0026] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.
[0027] In the following embodiments, cement is selected from: PO42.5 grade ordinary Portland cement; water reducer is selected from polycarboxylic acid type water reducer; metal tailings are selected from gold tailings slag, which is obtained by crushing, shaping and screening the gold tailings to obtain a particle size of 1-5 mm; fly ash is selected from F class I fly ash, The waste brick slag particles and waste brick slag powder in the following examples are obtained by crushing, grading and screening the modified waste brick slag prepared in the following preparation example to obtain waste brick slag particles with a particle size of 5-10 mm and waste brick slag powder with a particle size of 0.2-0.35 mm.
[0028] In the following preparation examples, the silica fume is made of microsilica powder from Sichuan Langtian Resources Comprehensive Utilization Co., Ltd., with a particle size of 1000-1200 mesh; The fly ash used is Class F Grade I fly ash.
[0029] The mesophase asphalt microspheres in the following preparation examples are anisotropic mesophase microspheres generated by thermal polycondensation during heat treatment of asphalt compounds. The mesophase microspheres are separated from the asphalt matrix and washed to form micron-sized spherical carbon materials. The mesophase microspheres are selected in the following preparation examples, and their parameters are: specific surface area: ≤5.0cm 2 / g, ash content: ≤0.3%, tap density: ≥1.3g / cm 3 , D50: ≤30.0μm, gram capacity: ≥350mAh / g.
[0030] The following preparation example is a modified waste brick slag obtained by subjecting the waste brick slag to an enhancement modification treatment and then a hydrophobic modification treatment.
[0031] Preparation Example 1 A method for preparing modified waste brick slag comprises the following steps: S1. The waste brick slag is firstly crushed and then immersed in a modified mixed solvent at a temperature of 40°C for 35 minutes, and then filtered and subjected to high-temperature treatment. The specific operation of the high-temperature treatment is: firstly treated at 85°C for 50 minutes, and then treated at 320°C for 1.5 hours; S2, immersing the waste brick residue treated in step S1 in a hydrophobic modification solution at a temperature of 65° C., filtering and drying after treatment for 1.5 hours to obtain modified waste brick residue.
[0032] The modified mixed solvent in step S1 is prepared by mixing the following raw materials: 8kg silane coupling agent KH-550, 5kg binder, 25kg water, 18kg crack filling filler, wherein the binder is polyvinyl alcohol, the crack filling filler includes silica fume, fly ash and alkaline substance with a mass ratio of 1:1:0.6, and the alkaline substance is magnesium acetate and sodium aluminate with a mass ratio of 1:1.3; In step S2, the hydrophobic modified solution is prepared by mixing the following raw materials: 15kg versatate, 10kg mesophase asphalt microspheres, 8kg silane coupling agent KH-550, 2kg initiator dibenzoyl peroxide, 8kg acrylamide, 8kg acryl alcohol and 25kg water.
[0033] Preparation Example 2 A method for preparing modified waste brick slag comprises the following steps: S1. The waste brick slag is firstly crushed and then immersed in a modified mixed solvent at a temperature of 35°C for 40 minutes, and then filtered and subjected to high-temperature treatment. The specific operation of the high-temperature treatment is: firstly treated at 80°C for 60 minutes, and then treated at 300°C for 2 hours; S2, immersing the waste brick residue treated in step S1 in a hydrophobic modification solution at a temperature of 60° C., filtering and drying after treatment for 2 hours to obtain modified waste brick residue.
[0034] The modified mixed solvent in step S1 is prepared by mixing the following raw materials: 5kg silane coupling agent KH-550, 3kg binder, 20kg water, 15kg crack filling filler, wherein the binder is polyethylene glycol, the crack filling filler includes silica fume, fly ash and alkaline substance in a mass ratio of 1:0.8:0.5, and the alkaline substance is magnesium acetate and sodium aluminate in a mass ratio of 1:1.2; In step S2, the hydrophobic modified solution is prepared by mixing the following raw materials: 12kg versatate, 8kg mesophase asphalt microspheres, 5kg silane coupling agent KH-550, 1kg initiator dibenzoyl peroxide, 5kg acrylamide, 5kg acryl alcohol and 20kg water.
[0035] Preparation Example 3 A method for preparing modified waste brick slag comprises the following steps: S1. After the waste brick slag is initially crushed, it is first immersed in a modified mixed solvent at a temperature of 45°C for 30 minutes, and then filtered and subjected to high-temperature treatment. The specific operation of the high-temperature treatment is: firstly, it is treated at 90°C for 40 minutes, and then at 340°C for 1 hour; S2, immersing the waste brick residue treated in step S1 in a hydrophobic modification solution at a temperature of 0° C., filtering and drying after treatment for 1 hour to obtain modified waste brick residue.
[0036] The modified mixed solvent in step S1 is prepared by mixing the following raw materials: 10kg silane coupling agent KH-550, 8kg binder, 30kg water, 20kg crack filling filler, wherein the binder is hydroxyethyl cellulose, the crack filling filler includes silica fume, fly ash and alkaline substance in a mass ratio of 1:1.2:0.8, and the alkaline substance is magnesium acetate and sodium aluminate in a mass ratio of 1:1.5; In step S2, the hydrophobic modified solution is prepared by mixing the following raw materials: 18kg versatate, 15kg mesophase asphalt microspheres, 10kg silane coupling agent KH-550, 3kg initiator dibenzoyl peroxide, 12kg acrylamide, 10kg acryl alcohol and 30kg water.
[0037] Preparation Example 4 A method for preparing modified waste brick slag is carried out according to the method in Preparation Example 1, except that 12 kg of aluminum sludge is also added to the modified mixed solvent in step S1.
[0038] Preparation Example 5 A method for preparing modified waste brick slag is carried out according to the method in Preparation Example 1, except that 8 kg of aluminum sludge is also added to the modified mixed solvent in step S1.
[0039] Preparation Example 6 A method for preparing modified waste brick slag is carried out according to the method in Preparation Example 1, except that 15 kg of aluminum sludge is also added to the modified mixed solvent in step S1.
[0040] Preparation Example 7 A method for preparing modified waste brick slag is carried out according to the method in Preparation Example 1, except that magnesium acetate is used as the alkaline substance in the crack filling filler in step S1.
[0041] Preparation Example 8 A method for preparing modified waste brick slag is carried out according to the method in Preparation Example 1, except that magnesium hydroxide is used as the alkaline substance in the crack filling filler in step S1.
[0042] Preparation Example 9 A method for preparing modified waste brick slag is carried out according to the method in Preparation Example 1, except that calcium hydroxide is used as the alkaline substance in the crack filling filler in step S1.
[0043] Preparation Example 10 A method for preparing modified waste brick slag is carried out according to the method in Preparation Example 1, except that in step S1, the alkaline substance in the crack filling filler is sodium aluminate.
[0044] Preparation Example 11 A method for preparing modified waste brick slag is carried out according to the method in Preparation Example 1, except that the specific operation of high temperature treatment in step S1 is: treating at 85° C. for 140 minutes.
[0045] Preparation Example 12 A method for preparing modified waste brick slag is carried out according to the method in Preparation Example 1, except that acrylamide and acryl alcohol are not added to the hydrophobic modification solution in step S2.
[0046] Preparation Example 13 A method for preparing modified waste brick slag is carried out according to the method in Preparation Example 1, except that no mesophase asphalt microspheres are added to the hydrophobic modification solution in step S2.
[0047] Preparation Example 14 A method for preparing modified waste brick slag is carried out according to the method in Preparation Example 1, except that in step S2, an equal amount of mesophase asphalt microspheres are replaced by coal tar asphalt.
[0048] Comparative Preparation Example 1 A method for preparing modified waste brick slag is carried out according to the method in Preparation Example 1, except that the waste brick slag after preliminary crushing is only subjected to the hydrophobic modification treatment in step S2, and the enhancement modification treatment in step S1 is not carried out.
[0049] Comparative Preparation Example 2 A method for preparing modified waste brick slag is carried out according to the method in Preparation Example 1, except that the waste brick slag after preliminary crushing is only subjected to the enhancement modification treatment in step S1, and is not subjected to the hydrophobic modification treatment in step S2.
[0050] Comparative Preparation Example 3 A method for preparing modified waste brick slag is carried out according to the method in Preparation Example 1, except that no crack filling filler is added to the modified mixed solvent in step S1.
[0051] Comparative Preparation Example 4 A method for preparing modified waste brick slag is carried out according to the method in Preparation Example 1, except that no alkaline substance is added to the crack filling filler in step S1.
[0052] Example 1 A method for preparing low-carbon concrete based on brick slag and metal tailings comprises the following steps: A primary mixture is prepared by mixing 380 kg of cement, 680 kg of coarse aggregate, 300 kg of fine aggregate, 100 kg of mineral admixture, 50 kg of rice husk ash and 18 kg of anti-cracking fiber; 8 kg of admixture was mixed with 165 kg of water to prepare a mixed solution, and then the prepared primary mixture was added, and the mixture was stirred and mixed to prepare low carbon concrete.
[0053] The coarse aggregate includes waste brick slag particles and crushed stone in a mass ratio of 1:0.7, and the fine aggregate includes waste brick slag powder and sand in a mass ratio of 1:0.5; the waste brick slag particles are obtained by crushing and screening the modified waste brick slag prepared in Preparation Example 1 to obtain waste brick slag particles with a particle size of 5-10 mm, the waste brick slag powder is obtained by crushing and screening the modified waste brick slag prepared in Preparation Example 1 to obtain waste brick slag powder with a particle size of 0.2-0.35 mm, the crushed stone is a crushed stone with a continuous particle size of 5-15 mm, and the sand has a particle size of 0.2-0.3 mm; The mineral admixtures are slag, fly ash and gold tailings with a mass ratio of 1:1.3:2.5; the admixture is polycarboxylic acid water reducer, and the anti-cracking fiber is glass fiber with a length of 10-15mm and a diameter of 0.02-0.03mm.
[0054] Example 2 A method for preparing low-carbon concrete based on brick slag and metal tailings comprises the following steps: A primary mixture is prepared by mixing 350 kg of cement, 620 kg of coarse aggregate, 260 kg of fine aggregate, 80 kg of mineral admixture, 40 kg of rice husk ash and 15 kg of anti-cracking fiber; 5 kg of admixture was mixed with 145 kg of water to prepare a mixed solution, and then the prepared primary mixture was added, and the mixture was stirred and mixed to prepare low carbon concrete.
[0055] Wherein, the coarse aggregate includes waste brick slag particles and crushed stone in a mass ratio of 1:0.6, and the fine aggregate includes waste brick slag powder and sand in a mass ratio of 1:0.4; the waste brick slag particles are obtained by crushing and screening the modified waste brick slag prepared in Preparation Example 2 to obtain waste brick slag particles with a particle size of 5-10 mm, the waste brick slag powder is obtained by crushing and screening the modified waste brick slag prepared in Preparation Example 1 to obtain waste brick slag powder with a particle size of 0.2-0.35 mm, the crushed stone is a crushed stone with a continuous particle size of 5-15 mm, and the particle size of the sand is 0.2-0.3 mm; The mineral admixtures are slag, fly ash and gold tailings with a mass ratio of 1:1.2:2; the admixture is polycarboxylic acid water reducer, and the anti-cracking fiber is glass fiber with a length of 10-15mm and a diameter of 0.02-0.03mm.
[0056] Example 3 A method for preparing low-carbon concrete based on brick slag and metal tailings comprises the following steps: A primary mixture is prepared by mixing 400 kg of cement, 760 kg of coarse aggregate, 350 kg of fine aggregate, 120 kg of mineral admixture, 60 kg of rice husk ash and 20 kg of anti-cracking fiber; 10 kg of admixture was mixed with 180 kg of water to prepare a mixed solution, and then the prepared primary mixture was added, and the mixture was stirred and mixed to prepare low-carbon concrete.
[0057] The coarse aggregate includes waste brick slag particles and crushed stone in a mass ratio of 1:0.8, and the fine aggregate includes waste brick slag powder and sand in a mass ratio of 1:0.6; the waste brick slag particles are obtained by crushing and screening the modified waste brick slag prepared in Preparation Example 1 to obtain waste brick slag particles with a particle size of 5-10 mm, the waste brick slag powder is obtained by crushing and screening the modified waste brick slag prepared in Preparation Example 1 to obtain waste brick slag powder with a particle size of 0.2-0.35 mm, the crushed stone is a crushed stone with a continuous particle size of 5-15 mm, and the particle size of the sand is 0.2-0.3 mm; The mineral admixtures are slag, fly ash and gold tailings with a mass ratio of 1:1.5:3; the admixture is polycarboxylic acid water reducer, and the anti-cracking fiber is glass fiber with a length of 10-15mm and a diameter of 0.02-0.03mm.
[0058] Embodiment 4-14 A method for preparing low-carbon concrete based on brick slag and metal tailings is carried out according to the method in Example 1, except that the coarse aggregate and fine aggregate are the coarse aggregate and fine aggregate of the target particle size obtained after crushing and screening the modified waste brick slag obtained in Preparation Example 4-14.
[0059] Comparative Examples 1-4 A method for preparing low-carbon concrete based on brick slag and metal tailings is carried out according to the method in Example 1, except that the coarse aggregate and fine aggregate are the coarse aggregate and fine aggregate of the target particle size obtained after crushing and screening the modified waste brick slag obtained in Comparative Preparation Examples 1-4.
[0060] Performance Testing The concrete prepared in the examples and comparative examples of the present application was tested for 28d compressive strength with reference to GB / T50081-2016 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete". In addition, the crack area per square meter of concrete was tested according to GB / T50081-2019 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete". The test results are shown in Table 1 below.
[0061] Table 1: Referring to the test results in Table 1 above, the low-carbon concrete prepared in the embodiment of the present application has excellent compressive strength and durability. Combined with the test results of Example 1 and Examples 4-6, it can be seen that when the waste brick slag is modified, when aluminum sludge is added to the modified mixed solvent during the enhanced modification treatment, the mechanical properties and crack resistance of the concrete can be further improved. Combined with the test results of Example 7 and Example 10, when the alkaline substance in the crack filling filler is a single sodium aluminate or magnesium acetate, its crack resistance is reduced and its compressive strength is also reduced; combined with the test results of Example 8 and Example 9, when the magnesium acetate is replaced with magnesium hydroxide or calcium hydroxide in equal amounts, it can be seen that its crack resistance and compressive strength are significantly reduced, which may be due to the fact that the magnesium acetate solution is easier to penetrate and then the subsequent high-temperature calcination can form nano-magnesium oxide, which can better fill and repair the microcracks of the waste brick slag.
[0062] Combined with the test results of Example 1 and Example 11, after immersion treatment in the modified mixed solvent, it can only play a drying role at a lower temperature. When Example 1 is also subjected to high-temperature calcination treatment, on the one hand, magnesium acetate can form nano magnesium oxide, and on the other hand, it also helps to interact with waste brick slag to help improve the performance of concrete. Combined with the test results of Example 12 and Example 13, when acrylamide and acryl alcohol are not added in Example 12, it can be seen that its compressive strength and crack resistance are reduced, and its hydrophobic modification affects the uniform dispersibility of waste brick slag in concrete. Combined with the test results of Examples 13 and 14, when mesophase asphalt microspheres are not added to the hydrophobic modified solution or ordinary asphalt is added, it can be seen that its crack resistance and compressive strength are reduced, and more unsaturated groups in the mesophase asphalt microspheres form chemical bonds with the hydrophobic agent. More importantly, the addition of microspheres can further fill the pore structure of the waste brick slag and improve its mechanical properties.
[0063] Referring to the test results of Example 1 and Comparative Examples 1 and 2, it can be seen that when the waste brick slag is only subjected to reinforcement modification treatment or hydrophobic modification treatment, its comprehensive performance is reduced, especially when it is only subjected to reinforcement modification treatment without hydrophobic modification treatment, its performance is still weaker than the concrete performance in Example 1. Combined with the test results of Comparative Examples 3 and 4, when no crack filling filler is added, its crack resistance is significantly reduced, and the compressive strength is also reduced. When no alkaline substance is added to the crack filling filler, its crack resistance and compressive strength are improved compared with Comparative Example 3, but are still far weaker than the test results of Example 1. The filling of microcracks in waste brick slag is obviously related to crack resistance and compressive strength.
[0064] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A low-carbon concrete made from brick slag and metal tailings, characterized in that: It includes the following raw materials in parts by weight: 350-400 parts of cement, 145-180 parts of water, 620-760 parts of coarse aggregate, 260-350 parts of fine aggregate, 80-120 parts of mineral admixtures, 40-60 parts of rice husk ash, 5-10 parts of admixtures and 15-20 parts of anti-cracking fibers; Wherein, the coarse aggregate includes waste brick slag particles and crushed stone, the fine aggregate includes waste brick slag powder and sand, and the mineral admixture includes at least metal tailings; The waste brick slag powder and waste brick slag particles are obtained by crushing the waste brick slag, performing a reinforcing modification treatment, and then performing a hydrophobic modification treatment, and then crushing and grading to obtain waste brick slag particles and waste brick slag powder respectively; The enhanced modification treatment specifically comprises the following steps: immersing the crushed waste brick slag in a modified mixed solvent containing a silane coupling agent, a binder, water and a crack filling filler, and then subjecting the mixture to high temperature treatment.
2. The low-carbon concrete made from brick slag and metal tailings according to claim 1, characterized in that: The crack filling filler comprises silica fume, fly ash and alkaline substances in a mass ratio of 1: (0.8-1.2): (0.5-0.8), and the alkaline substances are selected from magnesium acetate and sodium aluminate in a mass ratio of 1: (1.2-1.5).
3. The low-carbon concrete made from brick slag and metal tailings according to claim 1, characterized in that: The modified mixed solvent comprises the following raw materials in parts by weight: 5-10 parts of silane coupling agent, 3-8 parts of adhesive, 20-30 parts of water, 15-20 parts of crack filling filler, 8-15 parts of aluminum sludge.
4. The low-carbon concrete made from brick slag and metal tailings according to claim 1, characterized in that: The binder is selected from one or more of polyethylene glycol, hydroxyethyl cellulose, polyvinyl alcohol, and carboxymethyl cellulose.
5. The low-carbon concrete made from brick slag and metal tailings according to claim 1, characterized in that: The specific operation of high temperature treatment is first treating at 80-90°C for 40-60min, and then treating at 300-340°C for 1-2h.
6. The low-carbon concrete made from brick slag and metal tailings according to claim 1, characterized in that: The specific operation of the hydrophobic modification treatment is: the waste brick slag after the enhanced modification treatment is immersed in a hydrophobic modification solution and then dried. The hydrophobic modification solution includes the following raw materials in parts by weight: 12-18 parts of versatate vinyl carbonate, 8-15 parts of mesophase asphalt microspheres, 5-10 parts of silane coupling agent, 1-3 parts of initiator, 5-12 parts of acrylamide, 5-10 parts of acryl alcohol and 20-30 parts of water.
7. The low-carbon concrete made from brick slag and metal tailings according to claim 1, characterized in that: The coarse aggregate includes waste brick slag particles and crushed stone in a mass ratio of 1: (0.6-0.8), and the fine aggregate includes waste brick slag powder and sand in a mass ratio of 1: (0.4-0.6); The particle size of the waste brick slag particles is 5-10 mm, and the particle size of the waste brick slag powder is 0.2-0.35 mm.
8. The low-carbon concrete made from brick slag and metal tailings according to claim 1, characterized in that: The mineral admixtures are selected from slag, fly ash and gold tailings in a mass ratio of 1: (1.2-1.5): (2-3).
9. The low-carbon concrete made from brick slag and metal tailings according to claim 1, characterized in that: The admixture is a polycarboxylate water reducer, and the anti-cracking fiber is one or more of glass fiber and polypropylene fiber.
10. A method for preparing low-carbon concrete based on brick slag and metal tailings as claimed in any one of claims 1 to 9, characterized in that: The following steps are involved: Mixing cement, coarse aggregate, fine aggregate, mineral admixture, rice husk ash and anti-cracking fiber to prepare a primary mixture; The admixture is mixed with water to obtain a mixed solution, which is then added to the obtained primary mixture, and the mixture is stirred and mixed to obtain low-carbon concrete.
Citation Information
Patent Citations
Recycled concrete and preparation method thereof
CN112830724A
Recycled aggregate concrete and preparation method thereof
CN113563022A
Environment-friendly recycled concrete and preparation process thereof
CN113582609A
Silicon-based composite reagent reinforced recycled aggregate and preparation method thereof
CN118221372A